2014
DOI: 10.1159/000358512
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Spectrum and Prognosis of Longitudinally Extensive Transverse Myelopathies

Abstract: Background: Patients with a first episode of longitudinal extensive transverse myelopathy (LETM) were reviewed with two objectives: to evaluate the clinical spectrum of LETM and to analyze the related clinical and laboratory variables that can be used as functional prognostic markers. Methods: A retrospective review was conducted of clinical, radiologic and biochemical data of patients admitted for LETM between 1993 and 2011. Results: Our cohort included 72 patients [median age 41 years, interquartile range (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
1
7
2
2
Order By: Relevance
“…Previous studies yielded conflicting results regarding the association of LETM and functional outcome. 2,9,14,15 Contrary to the studies of Carnero Contentti et al, 2,15 LETM did not predispose to poor functional outcome in our cohort. This variation may be due to differences in patient groups.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous studies yielded conflicting results regarding the association of LETM and functional outcome. 2,9,14,15 Contrary to the studies of Carnero Contentti et al, 2,15 LETM did not predispose to poor functional outcome in our cohort. This variation may be due to differences in patient groups.…”
Section: Discussioncontrasting
confidence: 80%
“…Our results were similar to those in prior studies with longer follow-up periods. 9,14 Other spinal MR imaging features that we analyzed (distribution, T1 signal, extension in a transverse section, multiplicity, and contrast enhancement) were also evaluated in a previous study in which no association could be found with clinical outcome after acute transverse myelitis. 16 Our study supports these findings, though more studies with large numbers of cases are needed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…While we also demonstrated that NMOSD is coincidental to SS, the increased frequency of NMOSD (relative to MS) in SS patients likely reflects 2 syndromes driven by robust, albeit unrelated, disorders of humoral autoimmunity . The 2 remaining non‐NMOSD patients presented with a complete transverse myelitis and an LETM, which are myelopathies not characteristic of MS and as suggested can be attributable to SS .…”
Section: Discussionsupporting
confidence: 49%
“…dias (Christensen et al, 1990) e de 3,0 dias (Bruna et al, 2006 (Bruna et al, 2006). Todavia, encontra-se na literatura dados que se assemelham aos encontrados neste estudo (Cobo-Calvo et al, 2014;Sepúlveda et al, 2012).…”
Section: 7análise Estatísticaunclassified
“…O que permite presumir que quanto mais precoce à instalação da gravidade máxima da sintomatologia da mielite pior será seu prognóstico final. Tais achados reproduzem-se por autores que embora se utilizem de metodologia e escalas de incapacidades, por vezes, distintas das implementadas neste estudo (Cobo-Calvo et al, 2014;Debette et al, 2009).…”
Section: 7análise Estatísticaunclassified